Dynamics of fish assemblages on a continuous rocky reef and adjacent unconsolidated habitats at Fernando de Noronha Archipelago, tropical western Atlantic - Medeiros,Paulo R. (2011)
In recent years, many studies investigated how density-dependent factors, such as shortages in microhabitat and food availability influence the structure of reef fish assemblages. Most of what is currently known, however, comes from comparisons of isolated patch reefs and from correlations between fish abundance and one or few microhabitat variables. In addition, most studies were done in the Caribbean and Indo-Pacific regions, whereas the South Atlantic region has been, to date, understudied. The present study evaluated spatial and temporal variations in reef fish abundance and species richness in a continuous rocky reef and adjacent unconsolidated habitats in a Southwestern Atlantic reef, using underwater techniques to assess both fish numbers and microhabitat variables (depth, rugosity, number of crevices and percent cover of live benthic organisms, bare rock, sand, and limestone). Higher species richness was observed at consolidated substratum stations on both sampling periods (May and October), but fish abundance did not show a significant spatial variation. Topographical complexity and percent cover of algae (except coralline algae) were amongst the most important determinants of species richness, and correlations between fish size and refuge crevice size were observed. The non-random patterns of spatial variation in species richness, and to a lesser extent, fish abundance, were related to differences in substratum characteristics and the inherent characteristics of fishes (i.e. habitat preferences) and not to geographical barriers restraining fish movement. This study highlights the importance of concomitantly assessing several microhabitat variables to determine their relative influence in reef fish assemblages.